Initial study of Nickel Electrolyte for EnFACE Process - Tri Widayatno; Sudipta Roy (International Journal of Science and Engineering, 2015)
Nickel electrolyte for a micro-pattern transfer process without photolithography, EnFACE, has been developed. Previous work on copper deposition indicated that a conductivity of ~2.7 Sm-1 is required. Electrochemical parameters of electrolyte i.e. current density and overpotential are also crucial to govern a successful pattern replication. Therefore, the investigation focused on the measurement of physicochemical properties and electrochemical behaviour of the electrolyte at different nickel concentrations and complexing agents of chloride and sulfamate. Nickel electrolytes containing sulfamate, chloride and combined sulfamate-chloride with concentrations between 0.14 M and 0.3 M were investigated. Physicochemical properties i.e. pH and conductivity were measured to ensure if they were in the desired value. The electrochemical behaviour of the electrolytes was measured by polarisation experiments in a standard three-electrode cell. The working electrode was a copper disc (surface area of 0.196 cm2) and the counter electrode was platinum mesh. The potential was measured againts a saturated calomel reference electrode (SCE). The experiments were carried out at various scan rate and Rotating Disc Electrode (RDE) rotation speed to see the effect of scan rate and agitation. Based on the measured physicochemical properties, the electrolyte of 0.19 M nickel sulfamate was chosen for experimentation. Polarisation curve of agitated solution suggested that overall nickel electrodeposition reaction is controlled by a combination of kinetics and mass transfer.  Reduction potential of nickel was in the range of -0.7 to -1.0 V. The corresponding current densities for nickel deposition were in the range of -0.1 to -1.5 mA cm-2.